Kill&Repel Coatings: The Marriage of Antifouling and Bactericidal Properties to Mitigate and Treat Wound Infections. (20th October 2021) - Garay‐Sarmiento, Manuela; Witzdam, Lena; Vorobii, Mariia; Simons, Christian; Herrmann, Niklas; de los Santos Pereira, Andres; Heine, Elisabeth; El‐Awaad, Islam; Lütticken, Rudolf; Jakob, Felix; Schwaneberg, Ulrich; Rodriguez‐Emmenegger, Cesar
Abstract: Wound infections originate when exogenous or endogenous bacterial pathogens can circumvent the barrier of the wound dressing and invade the wound bed. Bacterial colonization causes inflammation, stalls the healing process, and carries the risk of dissemination to other tissues. In addition, current antimicrobial dressings fail to resolve an infection once it has been established because debris of the killed bacteria rapidly accumulates on their surface and hampers the antimicrobial action. Faced with this challenge, hybrid synthetic‐natural water‐soluble macromolecules are designed that self‐assemble onto the surface of dressings to generate an antifouling brush functionalized with endolysin, a bactericidal enzyme that poses no harm for eukaryotic cells. The simultaneous action of the brush and the enzyme not only prevents the colonization of the dressing, but also enables the coating to kill planktonic bacteria with even higher efficiency than the free enzyme. Remarkably, the Kill&Repel coating could completely eradicate bacteria in a simulated infection without allowing the adhesion of residues on the surface. Thus, this strategy opens a revolutionary approach for protecting and treating an infected wound in a safer and more efficient manner. Abstract : The bioinspired Kill&Repel coatings are formed by the self‐assembly of biohybrid molecules that generate brushes functionalized with endolysins, combining antifouling properties with selective bactericidal activity. The synergistic action of both building blocks results in an excellent barrier to molecular and cellular fouling and boosts the activity of the endolysin, enabling the coatings to resolve a simulated infection from multiresistant bacteria.